Making Indian bureaucracy responsible, accountable and result oriented (Note) - Jain, Sures Chandra (2000)
Pointing out major shortcomings of Indian bureaucratic system, the author ventures to assess empirically the need for making the system result oriented through establishing personal responsibility and accountability of the functionary concerned. He laments that the urgent necessity of reforms has been persistenty evaded. In support of his argument, he cites extensively from the Sixth (Central) Pay Commission Report to show how useful recommendations made therein on administrative reforms have remained neglected till today. - Reproduced
Keywords: Accountability; Note; Bureaucracy - India; Bureaucracy